Pengembangan LKPD Berbasis Model PJBL Bernuansa Sikap Ilmiah pada Materi Pecahan Kelas V SD - Laurensia Panwina; Bistari Bistari; Siti Halidjah; Hamdani Hamdani (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
This study aims to produce student worksheet products based on project-based learning models with nuances of a scientific attitude in addition and subtraction of fractions with different denominators for class V SDN 42 Pontianak City that are feasible. The research method used is research and development (RnD) by adapting the Thiagarajan 4D development model (define, design, development and dissemination). The data source for this research was the results of the validation of three validators and the results of the student response questionnaire after working on the LKPD that was made. The data collection technique for this research was a validation questionnaire by the validator and documentation on the LKPD used by the teacher. The results of the study show that during the process of developing LKPD based on the project based learning model with the nuances of a scientific attitude, it is carried out only in three stages, namely the define, design, and development stages. and the appropriateness of project based learning is 3.9 with very valid criteria, from the linguistic aspect it is 3.8 with very valid criteria, from the technical/appearance aspect it is 3.7 with very valid criteria, and from the scientific attitude loading aspect it is 4 with very strong criteria. valid. The response to the use of LKPD based on the project based learning model with a scientific attitude by students in the limited trial was 3.7 in the very good category and the response of students in the second trial obtained an average of 3.81 with very good criteria.